Development of a Semi-Autonomous System for High-Throughput Cyclic Voltammetry Measurements - Liu, Xinyue (My University, 2025)
This thesis presents the development and validation of a semi-autonomous system designed to perform high-throughput cyclic voltammetry (CV) measurements, specifically tailored for the electrochemical characterization of iron-based redox complexes. Unlike existing systems primarily focused on either synthesis or electrode automation, this work innovatively integrates precision electrode positioning via a modified 3D printer with automated solution preparation using a pipetting robot, and a PalmSens4 potentiostat for reliable electrochemical data acquisition, addressing the reproducibility and efficiency limitations prevalent in manual and partially automated electrochemical systems. Initial experiments validated the system's performance in preparing redox-active solutions, accurately positioning electrodes, and collecting CV data. Automation significantly reduced manual intervention, minimizing human-induced variability and improving the consistency and reproducibility of results. However, certain challenges emerged, notably the mechanical fragility of the pencil graphite electrodes used and the requirement for manual handling of CV scans, limiting complete automation. To address the current limitations, future work will involve redesigning the well plate and employing 3D printing techniques by using carbon sheet at the bottom to serve as each well's working electrode. By doing this, previous pencil graphite electrodes' fragility issue and the labor-intensive process of physically replacing them will be avoided. Additionally, in order to improve communication between the potentiostat and 3D printer, a customized control core should be introduced to the system along with the needed PalmSens SDK. Each operation and measurement are carefully monitored. The system detects the electrodes’ movement into and out of the well plate and responds in real time, under precise control. This modification is expected to make the system much more autonomous. Additionally, the experimental system will be set up in an atmosphere controlled by nitrogen or argon to reduce the interference brought on by dissolved oxygen. Such an inert atmosphere will broaden the scope of electrochemical research in a high throughput manner and make it easier to explore oxygen-sensitive metal complexes. Overall, this semi-autonomous system represents a meaningful advancement toward fully automated electrochemical research workflows, offering substantial improvements in experimental throughput and data quality, thus accelerating the discovery of new electrochemical energy storage materials.
Keywords: cyclic voltammetry, automation, electrochemical characterization, high-throughput screening